Druggability, molecular targets, and nanocarrier delivery of natural triterpenoid celastrol against chronic diseases - Chi Lui Chan; Yilu Sun; Xiaowen Mao; Hansen Chen; Jia Zhao; Jianhui Rong (Compuscript Ltd, 2024)
Celastrol is an active compound from the root of Tripterygium wilfordii Hook F that shows great potential in the treatment of inflammation, cancer, neurodegeneration, diabetes, and obesity. However, the clinical application of celastrol has been hindered by its low bioavailability and severe systemic toxicity. The aim of this review was to discuss the druggability, molecular targets, and nanocarrier delivery of the natural triterpenoid, celastrol, against chronic diseases. We sequentially investigated the physicochemical properties of celastrol using online tools (pkCSM and SwissADME), reviewed the recent studies on the molecular mechanisms underlying the therapeutic effects of celastrol, and examined the potential of nanoparticle-mediated delivery systems for safe and effective delivery of celastrol. The cancer-related targets and pathways involved were further predicted through network pharmacologic analysis. This review provides molecular insights into the pharmacologic activities and molecular mechanisms underlying celastrol, as well as useful information for the selection of nanocarrier drug delivery system for the clinical delivery of celastrol against various chronic diseases.